Cutaneous Manifestations of Chronic Renal Disease among Patients of Combined Military Hospital, Dhaka (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Chronic renal or kidney disease (CKD) presents with a range of cutaneous manifestation. Many New changes have been described since the advancement of hemodialysis, which prolonged the life expectancy, providing sufficient time for these changes to manifest.Objective: To observe the cutaneous changes in chronic kidney patients.Methods: This descriptive cross sectional study was conducted at Dermatology and Venereology department, Combined Military Hospital (CMH) Dhaka from July 2019 to June 2020. A total 100 CKD patients were recruited through purposive random sampling technique and observed for cutaneous changes.Results: Among the total, 88% study population had some form of skin disorders, pallor 65(65%) was found to be the most common cutaneous manifestation, while xerosis 61(61%), pruritus (53%), hyperpigmentation 37(37%) and bacterial infection 28(28%) were other common features. Prevalence of purpura was 29(29%) and fungal infection was 24(24%).Conclusion: CKD is associated with a broad spectrum of skin manifestations caused by the disease or by the treatment. The more commonly with pallor, xerosis and pruritus proper recognition of cutaneous signs and symptoms can relieve sufferings and reduce morbidity of the CKD patients.JAFMC Bangladesh. Vol 18, No 1 (June) 2022: 71-74